2013
DOI: 10.1603/en13233
|View full text |Cite
|
Sign up to set email alerts
|

Cashew Volatiles Mediate Short-Range Location Responses in <I>Pseudotheraptus wayi</I> (Heteroptera: Coreidae)

Abstract: Pseudotheraptus wayi Brown (Heteroptera: Coreidae) is a major pest of cashew in East Africa, but little is known about its chemical ecology. Here, we show by using behavioral assays and chemical analysis that some components of cashew leaf volatiles are attractants for male P. wayi. By using a petri dish arena-EthoVision video-tracking assay, males oriented closer to crude cashew leaf odor than females. In coupled gas chromatography-electroantennographic detection analysis, we found that four components of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Most insect herbivores rely on olfactory cues from plants during at least one stage of the foraging process. Many insect species use plant-produced volatile compounds to locate and evaluate potential host plants [133] as these cues effectively transmit useful information over both short [134] and long [135] distances in a variety of environments. Olfactory cues can be general indicators of plant presence, for example the respiratory biproduct CO 2 [19], or complex blends of volatile organic compounds (VOCs) that convey detailed information about plant identity [4], nutrient content [136], defense status, or risk of predation by natural enemies [137,138].…”
Section: Olfactory Cuesmentioning
confidence: 99%
“…Most insect herbivores rely on olfactory cues from plants during at least one stage of the foraging process. Many insect species use plant-produced volatile compounds to locate and evaluate potential host plants [133] as these cues effectively transmit useful information over both short [134] and long [135] distances in a variety of environments. Olfactory cues can be general indicators of plant presence, for example the respiratory biproduct CO 2 [19], or complex blends of volatile organic compounds (VOCs) that convey detailed information about plant identity [4], nutrient content [136], defense status, or risk of predation by natural enemies [137,138].…”
Section: Olfactory Cuesmentioning
confidence: 99%
“…These results suggest that the presence of linalool, alloocimene, and neo-allo-ocimene, whether alone or in double or triple combinations, is positively associated with attractiveness to L. sativae. This possibility is supported by Egonyu et al (2013) and Wanjiku et al (2014), who also identi ed the compounds allo-ocimene and neo-allo-ocimene in cashew leaves, and showed, using behavioural bioassays, that as mixtures these compounds are attractive to the insect-pest Pseudotheraptus wayi (Heteroptera: Coreidae) and their natural enemy Oecophylla longinoda (Latreille) (Hymenoptera: Formicidae). In addition, olfactometry studies Guohui et al (2005) have found that the isolated linalool attracted adult females of L. sativae.…”
Section: Discussionmentioning
confidence: 84%
“…Andrade et al 2016, Egonyu et al, 2013, Wanjiku et al 2014, and is present in considerable quantities in the genotypes of Citrus sp. less preferred by the psyllid Diaphorina citri, Kuwayama (Hemiptera: Psylidae)(Andrade et al 2016).…”
mentioning
confidence: 99%